1993
DOI: 10.2135/cropsci1993.0011183x003300050001x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory DNA of Ribosomal RNA Genes and Control of Nucleolus Organizer Activity in Wheat

Abstract: A molecular genetic analysis of wheat (Triticum aestivum L.) ribosomal RNA (rRNA) gene locus expression is described. Locus activity was estimated by cytological assays of nucleolus organiser volume. Gene structure was determined from DNA sequencing and restriction endonuclease mapping of isolated genes. Relative nucleolus organiser activity is correlated with the number of 135 base pair (bp) repeats that lie upstream of the gene promoter. A model is proposed in which gene and locus‐relative activity is determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…There are a number of models for the control of rDNA expression (18,19,26,29). One model for the control of nucleolar dominance including the effect of the unlinked regulatory locus revealed by Neves et al (27) shows the simple interaction between gene(s) on chromosome 2 and the NOR on chromosome 1 in rye.…”
Section: Resultsmentioning
confidence: 99%
“…There are a number of models for the control of rDNA expression (18,19,26,29). One model for the control of nucleolar dominance including the effect of the unlinked regulatory locus revealed by Neves et al (27) shows the simple interaction between gene(s) on chromosome 2 and the NOR on chromosome 1 in rye.…”
Section: Resultsmentioning
confidence: 99%
“…The 5 s and 18s-25s rRNA genes are highly repeated in the genome and, in the Triticeae, occur in many thousands of copies, most of which are not expressed (see Flavell et al 1993). Because the sequence variation between loci is often as great as that within loci, and because of the potentially large number of loci, the genes are difficult to map by RFLP or genetic methods.…”
Section: Ribosomal Rna Genesmentioning
confidence: 99%
“…Similarly, the tetraploid durum wheats with the A and B genomes contain four HMW genes, of which no more than three are active. Results reported so far have shown that the non-expression of the 1Ay gene can be caused by nucleotide changes in the pro-motor region (3,4) or by the presence of a transposon-like insertion in the encoding region (9). Flavell et al(3) established in Glu -1y allel of 6x-wheats an insertion of 8 kb., called WIS-2, belonging to transposon elements type "retrosposon".…”
Section: Introductionmentioning
confidence: 99%